2008
DOI: 10.1021/np800010r
|View full text |Cite
|
Sign up to set email alerts
|

Combining HPLC-PDA-MS-SPE-NMR with Circular Dichroism for Complete Natural Product Characterization in Crude Extracts: Levorotatory Gossypol inThespesia danis

Abstract: Despite recent demonstration of the power of HPLC-PDA-MS-SPE-NMR (high-performance liquid chromatography-photodiode-array detection-mass spectrometry-solid-phase extraction-nuclear magnetic resonance) in structure determination of natural products directly from minute amounts of crude extracts, this technique leaves chirality of the compounds uncharacterized. In this work we demonstrate that postcolumn SPE is a useful method of analyte concentration and accumulation not only for NMR but also for CD (circular d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(39 citation statements)
references
References 56 publications
1
37
0
1
Order By: Relevance
“…Fifteen micrograms (∼52 nmol) of oxypeucedanin (22 μg of oxypeucedanin hydrate, ∼72 nmol) in the 1.5 μL detection cell were sufficient to obtain an unambiguous 1 H NMR spectrum in about 2 min 20 s. This technique reduces the required sample quantity by a factor of up to 15 in comparison to a 5 mm tube in a conventional commercial probe. It is for this reason that the microcoil 1 H NMR technique proves useful with mass-limited samples and as a detector in capillary separations, as often demonstrated by our group [27][28][29][30] and several other very active European groups [31][32][33][34][35][36]. Moreover, our results confirmed that disk diffusion is a reliable, easy and inexpensive semi-quantitative susceptibility testing method that is sufficiently sensitive and ideally suited for preliminary investigations on the nano-to microscale.…”
Section: Resultssupporting
confidence: 80%
“…Fifteen micrograms (∼52 nmol) of oxypeucedanin (22 μg of oxypeucedanin hydrate, ∼72 nmol) in the 1.5 μL detection cell were sufficient to obtain an unambiguous 1 H NMR spectrum in about 2 min 20 s. This technique reduces the required sample quantity by a factor of up to 15 in comparison to a 5 mm tube in a conventional commercial probe. It is for this reason that the microcoil 1 H NMR technique proves useful with mass-limited samples and as a detector in capillary separations, as often demonstrated by our group [27][28][29][30] and several other very active European groups [31][32][33][34][35][36]. Moreover, our results confirmed that disk diffusion is a reliable, easy and inexpensive semi-quantitative susceptibility testing method that is sufficiently sensitive and ideally suited for preliminary investigations on the nano-to microscale.…”
Section: Resultssupporting
confidence: 80%
“…HPLC-PDA-MS-SPE-NMR experiments were performed on a system consisting of an Agilent 1100 LC system, a Knauer K100 Wellchrom pump, a Prospekt 2 solid-phase extraction device, an EsquireLC ion-trap mass spectrometer, and the above-mentioned Bruker Avance spectrometer equipped with a 30 μl 1 H{ 13 C} flow-probe, as described in details elsewhere (Schmidt et al 2008; Sprogøe et al 2008). NMR experiments were controlled with Bruker XWINNMR version 3.1 software, whereas all other operations were controlled with Bruker HyStar version 2.3 or 3.2 software.…”
Section: Methodsmentioning
confidence: 99%
“…Even though this is a classic example of natural product biaryl atropisomerism, it has only recently been shown that the active atropisomer of gossypol is that of the (M)-(-) enantiomer. 7 This atropisomeric configuration is an order of magnitude more potent than the (P)-(+) enantiomer, hence current studies are focussed on identifying plant species which preferentially produce (M) over (P) with a high enantiomeric excess in an attempt to reduce systemic toxicity. Thus far, the highest observed production was by the Thespia danis Oliv.…”
Section: Natural Atropisomerism In Medicinal Chemistrymentioning
confidence: 99%